2023
DOI: 10.1111/jfr3.12920
|View full text |Cite
|
Sign up to set email alerts
|

Flood susceptibility mapping using support vector regression and hyper‐parameter optimization

Aryan Salvati,
Alireza Moghaddam Nia,
Ali Salajegheh
et al.

Abstract: Floods are both complex and destructive, and in most parts of the world cause injury, death, loss of agricultural land, and social disruption. Flood susceptibility (FS) maps are used by land‐use managers and land owners to identify areas that are at risk from flooding and to plan accordingly. This study uses machine learning ensembles to produce objective and reliable FS maps for the Haraz watershed in northern Iran. Specifically, we test the ability of the support vector regression (SVR), together with linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Consequently, these features exhibit a limited impact on the model predictive performance when compared to other factors. The spatial average of distance to rivers and HAND have limited variability within our watershed and might The finding about the less importance of rainfall in flood estimation concurs with the results reported in the study by Salvati et al (2023) in pinpointing vulnerable regions within a non-coastal medium-sized watershed. The study suggests that rainfall may have a lower impact on flood occurrences or flood depth estimations compared to other influential factors.…”
Section: )supporting
confidence: 89%
“…Consequently, these features exhibit a limited impact on the model predictive performance when compared to other factors. The spatial average of distance to rivers and HAND have limited variability within our watershed and might The finding about the less importance of rainfall in flood estimation concurs with the results reported in the study by Salvati et al (2023) in pinpointing vulnerable regions within a non-coastal medium-sized watershed. The study suggests that rainfall may have a lower impact on flood occurrences or flood depth estimations compared to other influential factors.…”
Section: )supporting
confidence: 89%
“…The flood probability values were then categorized into five susceptibility classes, very low, low, moderate, high, and very high, by applying the natural breaks classification method (Aydin & Iban, 2022; Duwal et al, 2023) (Figure 5). The natural breaks classification method creates meaningful and distinct grouping in the data based on inherent patterns while minimizing the variance within classes and maximizing the variance between classes (Salvati et al, 2023). Despite the variations in the model performances and flood susceptibility extent, all the models indicated that the low‐altitude regions situated along the rivers and residential areas and paddy fields in the central, western, some parts of southeastern and northern regions of the study area are at high risk of flooding.…”
Section: Resultsmentioning
confidence: 99%
“…In order to address the shortcomings of conventional models, data‐driven approaches have been introduced, which extract information based on data provided, without relying on pre‐established assumptions or a deep understanding of the underlying physical processes and facilitate rapid spatial data analysis (Duwal et al, 2023; Zhu & Zhang, 2022). Over the past few years, numerous machine learning (ML) algorithms such as support vector machine (SVM) (Salvati et al, 2023; Shafapour Tehrany et al, 2017), random forest (RF) (Schmidt et al, 2020; Zhao et al, 2018), decision tree (DT) (Tehrany, Jones, & Shabani, 2019), boosted regression tree (Abedi et al, 2022), artificial neural network (ANN), (Pirnia et al, 2019), adaptive network‐based fuzzy inference system (ANFIS) (Hong et al, 2018), gradient boosting (GB) (Band et al, 2020), eXtreme Gradient Boosting (XGBoost) and AdaBoost (AB) (Aydin & Iban, 2022), have been effectively utilized to evaluate flood susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that RF has the best predictive performance for landslides and floods, with an AUC of 94.9% and 98.7%. Salvati et al [24] constructed a watershed flood-prone area identification model using support vector regression and three optimization methods (linear kernel, basic classifier, and hyperparameter optimization) based on 201 historical flood maps. The results demonstrated that this method effectively identified floods in the watershed, and the AUC of the test results was above 0.9.…”
Section: Introductionmentioning
confidence: 99%